A review of the relation between climate variability and mass removal processes: Tunja-Páez case study - Rojas Mesa, July Katerine; Leguizamón Barreto, Luis Carlos (Ingeniería Solidaria, 2022)
This literature review article is a product of the Research Project “Relation Between Climate Variability with Mass Removal Processes. Tunja-Páez case study”, developed in the Universidad Pedagógica y Tecnológica de Colombia in the year 2020.Introduction: This article focuses on the review of research studies and advances made during the last decade regarding the influence of climatic variability on the dynamics of slopes.Objective: To determine the influence of climatic variability in areas that present slope instability in the Tunja-Páez road corridor located in the department of Boyacá.Methods: A systematic review of information from books, manuals, reports, guides, and scientific articles on climate change, climate variability, mass removal processes, meteorological variables, and their influence on the resilience and adaptation of infrastructure related to containment and slope drainage projects.Results: The studies indicate criteria that relate temperature, precipitation and seismic activity with the occurrence of mass movements.Conclusion: Climatic anomalies in terms of precipitation and temperature has allowed research methodologies using probabilistic models to be developed for estimating the occurrence of said phenomena in future scenarios.Originality: The presented literature indicates the influence of climatic variability in the resulting mass removal processes as evidenced in studies at the global and national level.Limitations: This article scientific studies have been compiled that contrast the problems in the stability of slopes of the Tunja-Páez road corridor, without going into the details of these problems.
Keywords: climate change; climate variability; mass removal; precipitation; roadway infrastructure; adaptation